Micronutrient deficiencies in the English-speaking Caribbean and methods for their control. - SIMMONS, W.K. (1995)
Identifies the most widespread micronutrient deficiency as iron, and control measures as supplementation, nutrition education, parasitic control and fortification. Discusses the problems and successes of each approach to control this deficiency, and how they are helping to control anaemia in the English-speaking Caribbean.